2008
DOI: 10.1677/joe-08-0261
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-sensing receptor and insulin secretion: a role outside systemic control 15 years on

Abstract: In the 15 years since the identification and characterisation of the extracellular calcium-sensing receptor (CaR), it has become increasingly apparent that this cationic binding receptor is found in many tissues, not associated with the control of plasma calcium. One of these tissues is the pancreatic islet where insulin secretion provides the basis of energy regulation. It seems inherently unlikely that the islet responds to alterations in systemic calcium and a more plausible and intriguing possibility is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, since the identi�ication and characterisation of the receptor [2], it has become increasingly apparent that this cationic ion binding receptor is found on many tissues not associated with the control of plasma [Ca 2+ ] including; oesophageal [3] and colonic epithelia [4], the cardiovascular system (reviewed in [5]), hypothalamic neurons [6], pancreatic ducts [7] and pancreatic α-and β-cells [8][9][10]. The functional signi�icance of the CaR in tissue not involved in the control of systemic Ca 2+ is not fully understood [11,12]. In exocrine pancreas it has been suggested that the CaR monitors extracellular Ca 2+ in pancreatic juice to limit the risk of Ca 2+ carbonate stone formation [13], whilst the receptor may detect changes in levels of dietary Ca 2+ in gastrin secreting cells of the human antrum [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, since the identi�ication and characterisation of the receptor [2], it has become increasingly apparent that this cationic ion binding receptor is found on many tissues not associated with the control of plasma [Ca 2+ ] including; oesophageal [3] and colonic epithelia [4], the cardiovascular system (reviewed in [5]), hypothalamic neurons [6], pancreatic ducts [7] and pancreatic α-and β-cells [8][9][10]. The functional signi�icance of the CaR in tissue not involved in the control of systemic Ca 2+ is not fully understood [11,12]. In exocrine pancreas it has been suggested that the CaR monitors extracellular Ca 2+ in pancreatic juice to limit the risk of Ca 2+ carbonate stone formation [13], whilst the receptor may detect changes in levels of dietary Ca 2+ in gastrin secreting cells of the human antrum [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A majority of the pathways identified from this study, such as calcium signaling, PPAR signaling, N-glycan biosynthesis, TGF-b signaling, and cell communication, have been implicated as important T2D pathways in the literature. For example, calcium signaling is crucial for insulin secretion in pancreatic b-cells 34,35 as well as insulin-mediated glucose uptake in skeletal muscle. [36][37][38] PPAR signaling plays a critical role in glucose homeostasis and insulin sensitivity, and PPAR-gamma agonists such as thiazolidinediones have been used to treat T2D.…”
mentioning
confidence: 99%
“…For T2D analysis, HisCoM-PCA successfully identified several well-known pathways biologically related to T2D. For example, pathways such as calcium signaling, the renin-angiotensin system, and phosphatidylinositol signaling, are known to be related to insulin resistance or insulin sensitivity [24][25][26][27]. Of these, calcium signaling is crucial for insulin secretion in pancreatic β-cells [24,25], while phosphatidylinositol signaling is known to play an important role in an insulin-stimulated glucose metabolism pathway associated with obesity and T2D [27].…”
Section: Real Data Analysis Of Common Variants From Karementioning
confidence: 99%
“…For example, pathways such as calcium signaling, the renin-angiotensin system, and phosphatidylinositol signaling, are known to be related to insulin resistance or insulin sensitivity [24][25][26][27]. Of these, calcium signaling is crucial for insulin secretion in pancreatic β-cells [24,25], while phosphatidylinositol signaling is known to play an important role in an insulin-stimulated glucose metabolism pathway associated with obesity and T2D [27]. Moreover, some diseases, such as Alzheimer's disease (AD), asthma, and dilated cardiomyopathy have been reported to share molecular pathways or risk factors with T2D [28][29][30][31], and several studies have shown that insulin resistance is related to risk of AD, as well as T2D [28].…”
Section: Real Data Analysis Of Common Variants From Karementioning
confidence: 99%